Effect of Microwave on Longitudinal Air Permeability of Softwood and Hardwood - Poonia, Pawan Kumar; Tripathi, Sadhna; Sihag, Kapil (Indian Forester, 2017)
Microwave (MW) pre-treatment is a technique which is useful in the forest products industry to improve process efficiency and product performance. Low permeability of many wood species poses problems in timber drying as well as preservatives treatments.In the present study, microwave treatment of softwood and hardwoods viz; Pinus roxburghii and Eucalyptus tereticornis, was done at 2.45 GHz frequency at different levels of intensity and radiation time. The air permeabilities of Pinus roxburghii and E. tereticornis wood were measured using an in-house fabricated apparatus. The effect of MW intensity and time was studied on the air permeability of both the species in longitudinal direction. The highest air permeability was observed with treatment T-4B i.e. 143.35W/cm2 intensity for 5 min in both P. roxburghii and E. tereticornis samples where 14.39 and 0.43 Darcy were observed respectively. The statistical analysis showed significant improvement in longitudinal wood air permeability of both the species with increase in MW intensity and time of treatment.